Processing condition induced structural evolution in the alternating multi-layer structure during high speed thin-wall injection molding. (2nd September 2016) - Zhou, Yi; Deng, Hua; Yu, Feilong; Bai, Hongwei; Zhang, Qin; Chen, Feng; Wang, Ke; Fu, Qiang
Abstract: Polymeric materials with alternating multi-layer structure have gained much attention in the field of biomimic, where many methods were used to prepare materials with such structure for various functionalities. A simple method based on high speed thin-wall injection molding (HSTWIM) has been proposed in our previous studies for the easy fabrication of multi-layer functional polymeric materials. Herein, the effect of various injection processing parameters: injection distance, injection speed, mold temperature and mold thickness on the phase morphology and molecular orientation is studied. The processing condition induced changes in flow field, temperature field, viscosity and shear time are thought to largely influence the confinement of melt during processing, thus, their final phase morphology. It is observed that moderate injection distance, moderate injection speed, moderate mold temperature and thin mold favors the formation of such alternating multi-layer structure. Such study could provide guidelines for the fabrication of functional multi-layered structure through HSTWIM as well as control of phase morphology through confined flow. Graphical abstract: Highlights: The processing condition induced changes in flow field, temperature field, viscosity and shear time. The changes as above largely influence the confinement of melt during processing, thus, their final phase morphology. The moderate injection condition and thin mold favors the formation of alternating multi-layer structure. The confinement of flow plays a key role on formation of alternating multi-layer structure.